Safety and Efficacy of Ultra-hypofractionation in Node-positive Prostate Cancer. Issue 3 (March 2021) - Telkhade, T.; Murthy, V.; Kanala, T.S.; Mathew, J.M.; Phurailatpam, R.; Mokal, S.; Chourasiya, D.; Panigrahi, G.; Krishnatry, R.
Abstract: Aims: The safety and efficacy of stereotactic body radiotherapy (SBRT) in localised prostate cancer are now established through phase III randomised trials. Its utility in node-positive prostate cancer is restricted due to a lack of controlled studies specifically addressing this subgroup. Herein we report the safety and efficacy of SBRT in this subgroup. Materials and methods: In total, 60 patients treated with SBRT to prostate and pelvis were analysed. All patients received neoadjuvant androgen deprivation therapy for at least 6 months and long-term adjuvant hormonal therapy (70% medical and 30% surgical). All patients were treated with daily image-guided rotational intensity-modulated radiotherapy. The dose delivered to the prostate and gross node was 35–37.5 Gy and 25 Gy in five fractions to the elective pelvic nodal region on alternate days. Acute and late toxicities were graded as per Radiation Therapy Oncology Group common toxicity criteria. Results: Forty-one (68%) patients had a Gleason score ≥8. The median prostate-specific antigen level at diagnosis was 39 ng/ml. Twenty (33%) patients had common iliac nodal uptake on initial prostate-specific membrane antigen positron emission tomography-computed tomography. After the median follow-up of 30 months, no acute or late Radiation Therapy Oncology Group grade ≥3 gastrointestinal toxicity was noted. Acute grade 2 genitourinary and gastrointestinal toxicities were 8.3% and 11.7%, respectively. Late grade 2 genitourinary and gastrointestinal toxicities were 3.3% and 8.3%, respectively. Late grade 3 genitourinary toxicity was seen in two (3.3%) patients. Three-year overall survival and biochemical failure-free survival was 89% and 77%, respectively. Conclusion: SBRT to the prostate and pelvis is safe and efficacious in node-positive prostate cancer even with common iliac nodal involvement (stage M1a). Highlights: SBRT to the prostate and pelvis in node-positive prostate cancer is safe. Radiotherapy is effective in controlling common iliac nodal disease. Prostate dose above 35 Gy and longer duration of ADT may improve outcomes.